Radical Scavenging Activity Combination of Sambiloto (Andrographis paniculata Nees.) and Patikan Kebo (Euphorbia hirta L.) Ethanolic Extracts on 2,2-Diphenyl-1-Picrylhidrazyl (DPPH) - Andayana Puspitasari Gani; Suwidjiyo Pramono; Sudibyo Martono; Sitarina Widyarini (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Research of radical scavenging activity of sambiloto (Andrographis paniculata Nees) and patikan kebo (Euphorbia hirta L) ethanolic extracts and their combination toward 2,2-Diphenyl-1-Picrylhidrazyl (DPPH) has conducted. Subjects of this experiment comprise sambiloto ethanolic extract, patikan kebo ethanolic extract, dechlorophyllated extract of sambiloto and combinations among those three. Dechlorophyllation by electrocoagulation method is done to reduce chlorophyll content thereby increasing the level of active compound in the sambiloto extract. The results of dechlorophyllation showed that only total flavonoid content in the extract of sambiloto increased, meanwhile the radical scavenging activity results showed that patikan kebo ethanolic extract has the lowest IC50 value (22,36 µg/mL) compared to sambiloto ethanolic extract (IC50 value 499,03 µg/mL). Extract combination may increase DPPH radical scavenging activity of the sambiloto extract (IC50 value 76,06 µg/mL) but not higher than that of patikan kebo single extract.